Peran Institut Mosintuwu dalam Membangun Budaya Perdamaian melalui Kaum Perempuan di Kabupaten Poso, Sulawesi Tengah - Maryanti Babutung (Universitas Bosowa, 2018)
This research aims to know : (1) Institute Mosintuwu strategy in building the culture of peace through women in Poso District, Central Sulawesi. (2) The Impact experienced by the people of Poso city with the existence of the Institute Mosintuwu as one community organization to build a culture of peace. This research is done with qualitative descriptive research method. Data collection is done by using the interview, study the documentation and the questioner. techniques of data analysis includes the stages of the data collection through observation the author of the activities carried out by the Institute of Mosintuwu, interact with them to understand their interpretation of Institutnya, analyze the data and provide the conclusion at the end of the discussion. The findings in this studys that : the strategies by Institute Mosintuwu in building a culture of peace in Poso District very successful. Many of the programs that have made an effort to build a culture of peace, one of them is the School Women.Through the Women School is subsequently made citizens Poso town in general and specifically women think that when they do not want to hang out with people of different beliefs or will not learn to know what is actually happening in the Poso conflict, then there would be only hatred and mutual suspicion. The school women through Institute Mosintuwu present and provide a space for the learning space, story telling and know each other to the women at the time of the conflict said as the most many losses. And then the impact is very visible when out of the learning process in the Institute Mosintuwu, women active in the development of the village, dare to argue for the common good and provoke positive things that the Poso District should be removed from the hatred when the conflict. In addition, the voices of women are always calculated in the decision-making, either in the village or regional. Women are also able to produce something worth selling to help economy needs in the post-conflict.